The image of HIV/AIDS on the main Spanish newspapers. A four-year review: Cuatro años de revisión - Terrón, José Luis; Martínez García, Luisa; Sedó, Ramón G. (Folios, revista de la Facultad de Comunicaciones y Filología, 2012)
This paper sumarizes for years of rsearch ( 2005-2006/2007-2008) conducted on journalism articles on HIV/AIDS. Specifically,trough content análisis, we studied the information published in the main spanish newspapers ABC, el país, el mundo el periódico and la vanguardia. This research is important not only because the area of análisis in spain has almost no research, but for its connection with concrete actions of NGOs dedicated to HIV/AIDS. In this regard, we underscore our investigation is the resulto f a Project requierement from the spanish NGO Red2002 made to the centre of communication and health, which belongs to the institute of communication (InCom) of the Autonomous University of Barcelona. Finally, with this paper we emphasize the importance of studies of media in the field of health and highlighe them as they have a goal intervention, as shown in the paper’s conclusions.